Pengaruh Reputasi Kantor Akuntan Publik dan Rotasi Audit Terhadap Kualitas Audit - Hadi Pratama; Agus Munandar (UNIVERSITAS KALBIS, 2022)
This research is using quantitive study aimed to see whether there are influence of reputation of public accounting firm and audit rotaion quality audit. Measure audit quality using 4 dimensions, restatement, going concern audit opinion, accrual quality, and ERC.The population in this research are all of the manufacturing companies listed on Indonesia Stock Exchange (IDX) in the period 2014-2018. The number of research samples obtained are 101 companies with purposive sampling method. The data analysis used logistic regression and multiple regression by using Eviews 9 and SPSS 25. result showed that reputation of accounting firm doesn't affect on the restatement, reputation of accounting public negatively affect on opinion going concern, reputation of accounting public positively affect on quality akrual and ERC. audit rotation negatively affect on restatement, audit rotation doesn't affect on opinion going concern, quality actual, and ERC.